PRODUKSI YOGHURT dan SOYGHURT DARI SUSU SKIM dan SUSU KEDELAI DENGAN VARIASI BAHAN PENSTABIL - Rachmat Kosman (As-Syifaa Jurnal Farmasi, 2011)
A research had been done of Yoghurt and soyghurt production from skim milk and soya milk with variation of stabilizer agent. Yoghurt is fermentation milk product made from fermentation milk uses acid lactic bacteria, soyghurt is fermentation milk product made from fermentation soya milk uses acid lactic bacteria. To get the best quality of yoghurt and soyghurt usually added stabilizer agent so that get the best consistency, viscosity and stability. The aim of this investigation is to determine influence of milk kinds and stabilizer agent at Yoghurt and soyghurt production from skim milk and soya milk. Yoghurt made by skim milk and soyghurt made by soya milk with three variation of stabilizer agent, which 0,9% gelatine, 0,9% CMC, and 0.9% caragenan. The assay were organoleptic observation, pH and viscosity measurement, % acid lactic content test, and total of acid lactic bacteria test. The assay is done after storage at 50C. Organoleptic observation is consistency, odor, and taste. pH measurement by pH’s universe paper than viscosity measurement by  brookfield viscometer with three replication, 50 rpm rates. % lactat acid content test  by alkalimetry method. And total of acid lactid bacteria test by pouring method. The investigaton result can be concluded that stabilizer agent influence consistency, viscosity and prevent of separation between solid and liquid phase at yoghurt and soyghurt. 0,9% gelatine is the best stabilizer agent at yoghurt and soyghurt prodution.Key Words :Yoghurt, Soyghurt, Skim, Stabilizer Agent